KEEFEKTIFAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN MENGIDENTIFIKASI UNSUR – UNSUR DRAMA SISWA KELAS VIII SMP NEGERI 2 TALANG KELAPA - Oktaviani, Anis; Nuzulia Armariena, Dian; Nufus, Hayatun (Universitas PGRI Palembang, 2023)
This study aims to determine the learning outcomes of class VIII students at SMP Negeri 2 Talang Kelapa by using the Problem Based Learning model. In this study, data collection used test techniques. This is evident from the calculation of student learning data using the t-test contained in the SPSS V26 program. Through the calculations that have been carried out on the t-test the significant value obtained is 0.917 which means that the significant value is > 0.05. The average value in the experimental class was 97 and the control class was 85. Calculation of the hypothesis using the t-test (Independent sample test) formula, namely tcount = 1.334 > tcount 1.332 with df 29. Thus Ho is rejected and Ho is accepted. So the researchers came to the conclusion that